Reappraisal of the two axiid genera Manaxius Kensley, 2003 and Calaxidium Sakai, 2014, and description of a new species of Calaxius Sakai & de Saint Laurent, 1989 from French Polynesia, Southwest Pacific (Crustacea: Decapoda: Axiidea) - Komai, Tomoyuki (Zootaxa, 2016)
Discovery of an undescribed species of axiid shrimp from French Polynesia, Southwest Pacific, led the author to assess the taxonomic status of the two nominal genera, Manaxius Kensley, 2003 and Calaxidium Sakai, 2014. As a result, these two genera are synonymized under Calaxius Sakai & de Saint Laurent, 1989, because there are no significant differences in generic characters among the three taxa. An emended generic diagnosis of Calaxius is presented. The new species, Calaxius poupini, is morphologically similar to C. euophthalmus (De Man, 1905), C. izuensis Komai, 2011, C. kensleyi Clark, Galil & Poore, 2007, C. mimasensis (Sakai, 1967), C. pailoloensis (Rathbun, 1906) and C. sibogae (De Man, 1925), but the poorly developed armature on the ventral margin of each cheliped merus distinguishes the new species from the other six allied species. Some points of taxonomic confusion relating to Calaxius are clarified.